Scott Pilgrim's Precious Little Life: Scott Pilgrim # 1 - O'Malley, Bryan Lee (Portland, OR : Oni Press, 2012)
Scott Pilgrim's life is fantastic. He's 23 years old, in a rock band, between jobs, and dating a cute high school girl. Everything's awesome until a seriously mind-blowing delivery girl named Ramona Flowers enters his life.
Cover title.
new kids book 2023 winter.
Keywords: High school students; Teenagers; Comic books, strips, etc; Comics (Graphic works); Romance comic books; Graphic novels